Clinical Pharmacology of Citrus aurantium and Citrus sinensis for the Treatment of Anxiety. (2nd December 2018) - Mannucci, Carmen; Calapai, Fabrizio; Cardia, Luigi; Inferrera, Giuseppina; D'Arena, Giovanni; Di Pietro, Martina; Navarra, Michele; Gangemi, Sebastiano; Ventura Spagnolo, Elvira; Calapai, Gioacchino
Abstract : Objective . The aim of this review is to analyze preclinical and clinical studies investigating the anxiety effects of Citrus aurantium or Citrus sinensis essential oils (EOs). Design . The bibliographic research was made on the major scientific databases. Analysis included only articles written in English and published on peer-reviewed scientific journals describing preclinical experiments and clinical trials carried out to investigate the antianxiety effects of Citrus aurantium or Citrus sinensis EOs on anxiety disorders. Clinical studies reporting the antianxiety effects of products containing Citrus aurantium or Citrus sinensis EOs in combination with other active substances, including medicinal plants, were excluded. Nine clinical studies fulfilled the criteria adopted for analysis. Results . Data show that Citrus aurantium or Citrus sinensis EOs produce anxiolytic effects both in preclinical experiments and in different clinical conditions. Citrus aurantium EO aromatherapy reduced anxiety level in the great part of stress conditions studied (subjects affected by chronic myeloid leukemia and preoperative patients) except for a sample of patients subjected to colonoscopy. Exposition to Citrus sinensis EO in clinical studies shows to be positive in reducing anxiety level in patients waiting for dental treatment as well as in healthy volunteers submitted to an anxiogenic situation. Conclusions . Overview of clinical trials conducted with Citrus aurantium or Citrus sinensis on people with anxiety showed that inhalation or oral administration of Citrus aurantium and inhalation of Citrus sinensis can exert beneficial effects on anxiety; however, because of incomplete accuracy in the reporting of methodology, further more complete clinical studies are warranted.